PERSEPSI MASYARAKAT TERHADAP PERANAN ANGGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) DALAM PERENCANAAN PEMBANGUNAN DESA DI DESA KETANEN KECAMATAN PANCENG KABUPATEN GRESIK - Ulfiyatin Ulfiyatin; Haryanto Haryanto (Media Mahardhika, 2023)
This research aims to determine community perceptions of the role of the village revenue and expenditure budget (APBDes) in village development planning in Ketanen Village, Panceng District, Gresik Regency in 2021 -2022. The data analysis technique used is descriptive statistics. Data obtained through questionnaires, observation, and documentation. The variables used in this study were basic needs fulfillment (PKD), village facilities and infrastructure development (PSPD), local economic potential development (PPEL), and community empowerment (PM) with a sample of 20 respondents. Based on data analysis that has been carried out by researchers, it can be concluded that community perceptions of the village income and expenditure budget (PMPAPBDes) have a significant effect on fulfilling basic needs (PKD), while other variables are development of village facilities and infrastructure (PSPD), development local economic potential (PPEL), and community empowerment (PM) have no effect on community perceptions of the role of the village income and expenditure budget (PMPAPBDes)